Serological Evidence of Backyard Pig Exposure to Highly Pathogenic Avian Influenza H5N8 Virus during 2016–2017 Epizootic in France - Hervé, Séverine; Schmitz, Audrey; Briand, François-Xavier; Gorin, Stéphane; Quéguiner, Stéphane; Niqueux, Éric; Paboeuf, Frédéric; Scoizec, Axelle; Le Bouquin-Leneveu, Sophie; Eterradossi, Nicolas; Simon, Gaëlle (Pathogens (Basel), 2021)
In autumn/winter 2016–2017, HPAI-H5N8 viruses belonging to the A/goose/Guandong/1/1996 (Gs/Gd) lineage, clade 2.3.4.4b, were responsible for outbreaks in domestic poultry in Europe, and veterinarians were requested to reinforce surveillance of pigs bred in HPAI-H5Nx confirmed mixed herds. In this context, ten pig herds were visited in southwestern France from December 2016 to May 2017 and serological analyses for influenza A virus (IAV) infections were carried out by ELISA and hemagglutination inhibition assays. In one herd, one backyard pig was shown to have produced antibodies directed against a virus bearing a H5 from clade 2.3.4.4b, suggesting it would have been infected naturally after close contact with HPAI-H5N8 contaminated domestic ducks. Whereas pigs and other mammals, including humans, may have limited sensitivity to HPAI-H5 clade 2.3.4.4b, this information recalls the importance of implementing appropriate biosecurity measures in pig and poultry farms to avoid IAV interspecies transmission, a prerequisite for co-infections and subsequent emergence of new viral genotypes whose impact on both animal and human health cannot be predicted.